Multiply (3x – 1)(x + 5)

Question

Asked 4/16/2013 12:22:51 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Expert answered|andrewpallarca|Points 21101|

Expert answered|andrewpallarca|Points 21101|

Question

Asked 4/16/2013 12:22:51 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

There are no new answers.

Subtract (9x^2 + 3x – 4) – (3x^2 +8x – 1) **Weegy:** Subtract (9x^2 + 3x – 4) – (3x^2 +8x – 1) = 6x^2-5x-3
(More)

Question

Expert Answered

Updated 4/5/2014 2:50:04 PM

0 Answers/Comments

Solve for x. (x+3)^2 **Weegy:** Solution:
x/2 = 6 , x = 2(6) , x = 12 (answer) **User:** Solve (x + 3)2 = 36 for x. **Weegy:** How to Solve; 5(x-3)/4+(3/5) = (x+2)/3, for the Variable x. (An Algebra problem for Student Nurses) ... [ (x-3)+36 = 20(x+2), which is equal to 75x-225+36 = 20x+40. ] **User:** Solve (x + 3)^2 = 36 for x. **Weegy:** 72. **User:** (x + 3)^2 = 36 Solve for X **Weegy:** If (x + 3)^2 = 36, x = -9, 3. Your answers are x equals -9 and 3. (More)

Question

Expert Answered

Asked 4/16/2013 12:07:39 PM

0 Answers/Comments

What is the correct solution to 3x + 2 = -5(x – 2) ? **Weegy:** 9x^4. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! (More)

Question

Not Answered

Updated 1/2/2019 6:16:39 AM

1 Answer/Comment

x + 2 = -5(x – 2) ;

x + 2 = -5x + 10 ;

x + 5x = 10 - 2 ;

6x = 8 ;

x = 8/6 ;

x = 4/3

x + 2 = -5x + 10 ;

x + 5x = 10 - 2 ;

6x = 8 ;

x = 8/6 ;

x = 4/3

Added 1/2/2019 6:16:39 AM

This answer has been confirmed as correct and helpful.

Solve 3x - 8.5 = 2.5x – 1.25 - .75x for x.

Question

Not Answered

Updated 4/5/2014 2:49:19 PM

2 Answers/Comments

3x - 8.5 = 2.5x – 1.25 - .75x ;

3x - 8.5 = 1.75x - 1.25;

3x - 1.75x = -1.25 + 8.5;

1.25x = 7.25;

x = 7.25/1.25;

x = 5.8

3x - 8.5 = 1.75x - 1.25;

3x - 1.75x = -1.25 + 8.5;

1.25x = 7.25;

x = 7.25/1.25;

x = 5.8

Added 4/5/2014 2:48:02 PM

This answer has been confirmed as correct and helpful.

3x-4=2x-4/3;

3x - 2x = -4/3 + 4;

x = 8/3

3x - 2x = -4/3 + 4;

x = 8/3

Added 4/5/2014 2:49:19 PM

This answer has been confirmed as correct and helpful.

32,005,318

questions answered

There are no comments.